Nursing diagnosis of physical order in women with angina pectoris - Marcos Venícios de Oliveira Lopes; Thelma Leite de Araújo (Rev Rene)
The study treats of a rising of the nursing diagnoses in women with angina pectoris seeking to establish correlations among the same ones. The process diagnoses was used according to Gordon (1994) and the diagnosis taxonomy of the NANDA to guide the establishment of the same ones. The results showed that the sharp pain acts as central diagnosis contributing direct and indirectly for the establishment of others. There was strong correlation among the diagnoses decreased heart debit, intolerance to the activity, prejudiced physical mobility and deficit in the self-care. It is concluded by the possible existence of relationships in the occurrence certain nursing diagnoses in women with angina pectoris.